2019
DOI: 10.3389/fnbeh.2019.00255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Schedule-Induced Behavior on Responses of Spontaneously Hypertensive and Wistar–Kyoto Rats in a Delay-Discounting Task: A Preliminary Report

Abstract: Delay discounting is the loss of the subjective value of an outcome as the time to its delivery increases. It has been suggested that organisms can become more tolerant of this delay when engaging in schedule-induced behaviors. Schedule-induced behaviors are those that develop at a high rate during intermittent reinforcement schedules without the need of arranged contingency to the reinforcer, and they have been considered as a model of compulsivity. There is evidence that relates compulsivity to greater delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Some researchers have reported steeper discounting rates in the SHRs (Aparicio et al, 2019;Bizot et al, 2007;Carbajal et al, 2023;Fox et al, 2008;Orduna, 2015). Others have reported no difference between SHR and comparison strains (Adriani et al, 2003;Garcia & Kirkpatrick, 2013;Gonzalez-Barriga & Orduna, 2022;Ramos, Lopez-Tolsa, Sjoberg, & Pellon, 2019).…”
Section: Steeper Delay Discounting In Rodent Models and Adhdmentioning
confidence: 99%
“…Some researchers have reported steeper discounting rates in the SHRs (Aparicio et al, 2019;Bizot et al, 2007;Carbajal et al, 2023;Fox et al, 2008;Orduna, 2015). Others have reported no difference between SHR and comparison strains (Adriani et al, 2003;Garcia & Kirkpatrick, 2013;Gonzalez-Barriga & Orduna, 2022;Ramos, Lopez-Tolsa, Sjoberg, & Pellon, 2019).…”
Section: Steeper Delay Discounting In Rodent Models and Adhdmentioning
confidence: 99%
“…This study analyzes schedule-induced behavior in self-control situations, given that ideas about delay discounting are incorporated into the model. The tasks assumed are general self-control tasks, as presented in Ramos et al (2019). Self-control tasks (e.g., Rachlin and Green (1972)) require a choice between two alternatives: a small reinforcer presented immediately (smaller and sooner; SS) and a larger reinforcer presented after a delay (larger PSYCHOLOGICAL FLEXIBILITY 10 and later; LL).…”
Section: The Situation To Be Simulatedmentioning
confidence: 99%
“…The amount of response of schedule-induced behavior is generally plotted in an inverted U-shape against the measured elapsed time Ramos et al (2019).…”
Section: The Situation To Be Simulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…After several years of investigating schedule-induced behaviors, Pellón and colleagues (Ardoy & Pellón, 2004; Gutiérrez-Ferre & Pellón, 2019; Íbias & Pellón, 2011; Pellón & Blackman, 1987; Pellón & Castilla, 2000; Pellón & Pérez-Padilla, 2013; Ramos et al, 2019) concluded that they are operants, either individually maintained by delayed reinforcement (Killeen & Pellón, 2013; Pellón & Killeen, 2015) or as part of a behavioral pattern that is reinforced as a whole and is repeated on every interreinforcement interval (Ruiz et al, 2016; Segal et al, 1965), a view that is also consistent with Skinner’s proposal on contiguity, instead of contingency, as necessary for the establishment of an operant behavior (Skinner, 1948).…”
mentioning
confidence: 99%